2004
DOI: 10.1093/nar/gkg936
|View full text |Cite
|
Sign up to set email alerts
|

Formation of DNA nanoparticles in the presence of novel polyamine analogues: a laser light scattering and atomic force microscopic study

Abstract: We synthesized a pentamine (3-3-3-3) and two hexamine (3-3-3-3-3 and 3-4-3-4-3) analogues of the natural polyamine, spermine (3-4-3) and studied their effectiveness in condensing pGL3 plasmid DNA, using light scattering and atomic force microscopic (AFM) techniques. The midpoint concentration of the polyamines on pGL3 condensation (EC50) was 11.3, 10.6, 1.5, 0.49 and 0.52 micro M, respectively, for 3-4-3, norspermine (3-3-3), 3-3-3-3, 3-3-3-3-3 and 3-4-3-4-3 in 10 mM Na cacodylate buffer. Dynamic laser light s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 57 publications
5
65
1
Order By: Relevance
“…In water, the polyplex size varies between about 90 and 200 nm, which is consistent with the sizes of polyplexes created with un-PEGylated polycations (54,(56)(57)(58). Upon the addition of Opti-MEM, PEG-PF4 ZIP and PEG-ATIII polyplexes did not aggregate and showed a small and uniform polyplex size over 120 min.…”
Section: Polyplex Sizesupporting
confidence: 76%
“…In water, the polyplex size varies between about 90 and 200 nm, which is consistent with the sizes of polyplexes created with un-PEGylated polycations (54,(56)(57)(58). Upon the addition of Opti-MEM, PEG-PF4 ZIP and PEG-ATIII polyplexes did not aggregate and showed a small and uniform polyplex size over 120 min.…”
Section: Polyplex Sizesupporting
confidence: 76%
“…This model offers two merits. First, we 8 can determine the shape of the cross-section of a toroid. Next, from an experimental point of view, we can determine the effect on DNA of a chemical added to the DNA solution by considering the image of a toroid; by determining whether the chemical effectively changes the thickness or stiffness of a DNA chain.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that a toroid structure is generated from a giant DNA molecule upon the addition of condensing agents such as multivalent cations, polyamines and neutral flexible polymers [1][2][3][4][5][6][7][8] . After a full survey of previous experimental studies on a DNA toroid, Bloomfield stated that "---the major diameter of the condensed particle remains almost constant on the order of 60-80 nm and does not seem to depend upon the length of an individual DNA molecule, so long as the DNA length is from 400 to over 40,000 base pairs (bp)."…”
Section: Introductionmentioning
confidence: 99%
“…[19] Vijayanathan et al have surveyed the suggested structures of pure and complexed plasmid DNA. [20] Recently, a plectonemic structure on mica has been used as a model for pure plasmids, and toroidal structures have been proposed for polyplexes [21] and dendriplexes. [22] For polyplexes, structures have been suggested in which the toroidal plasmid is wrapped around den- Figure 1.…”
Section: Introductionmentioning
confidence: 99%